Comparative Performance and Haematological Indices of Finishing Broilers Fed Palm Kernel Cake, Bambara Offal and Rice Husk as Partial Replacement for Maize - Ugwu, S.O.C.; Onyimonyi, A.E.; Ozonoh, C.I. (International Journal of Poultry Science, 2008)
Ninety six unsexed four weeks old Anak broilers were used to compare the performance of finishing broilers fed Palm kernel cake, Bambara offal and Rice husk as partial replacement for maize. The ninety-six broilers were divided into four groups and fed diets containing either 40 percent Maize (T1) as control or 20 percent Palm kernel cake (T2), 20 percent Bambara offal (T3) and 20 percent Rice husk (T4). Each group was replicated thrice with 8 birds per replicate in a Completely Randomized Design (CRD). Feed and water were provided ad libitum for the 28 days the trial lasted. Results showed that the effect of treatments on final body weight, body weight gain, feed intake, feed conversion ratio and feed cost/kg gain were significant (P < 0.05). Average daily gain of 0.075kg observed in birds on T2 was significantly different (P < 0.05) from values of 0.065Kg, 0.066kg and 0.067kg recorded for birds on the control, T3 and T4 diets respectively. Also, the same group (T2) had superior feed cost per kg gain of 118.60 which differed significantly (P < 0.05) from 135.59 and 154.40 observed for birds on the control and T4 diets respectively. Haematological investigation revealed that the same birds on T2 had significantly higher values (P < 0.05) of red blood cell, haemoglobin, packed cell volume and eosinophils. Results of this study showed that 20 percent PKC can effectively replace maize in diets of finishing broilers with better performance and economic returns.